Interacción de los iones calcio y potasio en la sobrevivencia y crecimiento del camarón blanco Litopenaeus vannamei en aguas de baja salinidad (Orinoquia, 2024)
The ionic composition of water is a fundamental factor in the productive activity at low salinity of Litopenaeus vannamei or white shrimp. In this research, the effect of Calcium and Potassium ions on the production parameters was evaluated; growth and survival, in larvae at 1±0.5 g l-1 salinity. The experimental design consisted of four (4) treatments (T1 = [1:0.5]; T2 = [1:0.75]; T3 = [1:1] and T4 = [1:1.5] Calcium and Potassium respectively. The animals were distributed at a rate of 5 animals per liter, at PL12 stage, which were randomly arranged in the 12 experimental units. Using analysis of variance (ANOVA), a significant difference was determined in the total length in treatment 3 (3.66±1.31 cm); For its part, the weight variable, without significant differences, defined treatment 3 with the highest mean (1.55±1.53). The height gain revealed the absence of significant differences, however, the highest average in the T3 specimens (2.91±0.83). In weight gain, by treatments, statistical significance was defined in experimental model 2, estimated at 0.83±0.13 g (83%). Survival found significant differences with a higher mean value in treatment 4 with 55.56% of the white shrimp Litopenaeu vannamei specimens. The physicochemical condition of the experimental units defined statistical significance with a higher mean in treatment 4 in the parameters Calcium (34.02±1.31 mg/L), and Potassium (9.8958±2.34 mg/L).
Keywords: Aquaculture; Litopenaeus vannamei; survival; growth